Pengaruh Pemberian Racikan Antibiotik Alami Terhadap Penularan Salmonella Sp dan Performans Broiler Starter - Ahmad Suminto; Suhardi Suhardi; Eudia Christina Wulandari (Tropical Animal Science, 2020)
The livestock sub-sector has a very important role in meeting the protein needs of the population by improving community nutrition and increasing farmers' incomes. One of the many animal husbandry businesses developed in Indonesia is the business of broiler chickens. The obstacles faced in raising broiler chickens are susceptible to diseases, one of which is Salmonellosis. The purpose of this study was to determine the effect of giving antibiotic concoctions to salmonella transmission and broiler starter chicken performance. One day old broiler chickens (DOC) 100 tails with an initial body weight of an average of 70-95 grams are randomly allocated into 4 treatments and 5 replications, where each test consists of 5 tails. The four treatments consisted of T0 (100% drinking water), T1 (95% drinking water: 5% compounded antibiotics), T2 (90% drinking water: 10% compounded antibiotics) and T3 (85% drinking water: 15% concocted antibiotics ). Commercial feed for broilers and drinking water treatment is given ad libitum. The parameters observed were body weight, feed consumption, FCR (Feed Convert Ratio), liver weight, blood sugar, relative length of digestive tract of chicken and salmonella sp bacteria in the large intestine of broiler chicken at 35 days. The results showed that the administration of antibiotic concoctions had no significant effect (P≥0.05) on body weight, feed consumption, FCR (Feed Convert Ratio), liver weight, blood sugar, relative length of digestive tracts of chickens and salmonella sp bacteria in the large intestine. It was concluded that the administration of antibiotic concoctions did not significantly affect the transmission of salmonella sp and broiler starter performance.